Les édifices néogothiques parisiens et leurs verrières : églises et chapelles catholiques - Martine Callias Bey (In Situ)
Despite the interest elicited by 19th century religious art over the past thirty years, Paris has lost much of its 19th century religious stained glass. It was urgent to carry out an inventory of what remains. The aim of this article is to present the Catholic Gothic revival buildings in Paris and their stained glass. The corpus comprises five parish churches, 19 congregational chapels or chapel transformed into parish churches, and two other ancillary buildings. A total of 526 stained-glass works was surveyed and studied; 286 are designs with figures, 37 of these classifiable as stained-glass picture compositions. The remaining 240 works are ornamental. Behind this production, we find some 22 different stained-glass producers, amongst the most important of which are Didron, Lusson, Champigneulle, Hirsch and Gsell. Paris played a leading role in the revival of stained glass during the early years of the 19th century, thanks in part to the perspicacious inspiration of certain figures in power, such as the Prefect of Paris, the Comte de Chabrol, who was at the origins of the ‘resurrection’ of the skill of stained-glass painters with the 1825 creation of the works at the Foire Saint-Laurent. Further inspiration came from the first restoration work carried out on older stained-glass works, and the decisive role of diocesan architects. The iconography of these works reflects the evolution of France’s religious life during the period, from the liberty of the Concordat to the Congregationist explosion, the return of Papal authority, the anti-congregationist movement, and the law of separation of church and state in 1905. Stained glass of neo-Gothic inspiration shows a Gallican tendency marked by a certain ‘romanticism’. But from 1850 on, new imagery began to appear, often taking on the form of ‘propaganda’. Neo-Gothic stained glass also marks a return of colour, the mastery of the art of older stained-glass artists involving considerable technical competence. The movement also involved new processes, however, such as the printing of the motifs repeated along borders or in the background. The architectural eclecticism of the 19th century can be seen as a coherent style, but it is also a mixture of styles, not necessarily coherent, used for personages and for the framing of stained-glass works known as ‘archaeological’ or ‘picture’ compositions.